THE RELATIONSHIP BETWEEN BRITISH WAR CORRESPONDENTS IN THE FIELD AND BRITISH MILITARY INTELLIGENCE DURING THE ANGLO-BOER WAR - McCrachen, Donal P (Scientia Militaria - South African Journal of Military Studies, 2015)
This article chronicles the developing relationship between the press corps on the British side and British Military Intelligence during the Anglo-Boer War, particularly during the formal and non-guerrilla phase of the conflict. The article comments on the nature and composition of both the press corps and of the military intelligence operation. In particular, the article looks at the problem issues relating to the relationship: licensing correspondents, censorship, monitoring journalists’ activities, as well as the successful attempt of the intelligence sector to bring the press into their campaign to spread pro-British propaganda. The role of the press in the saga of the attempt to make British Military Intelligence a scapegoat for British initial failures is also mentioned.